Neuromechanisms and subjective experiences during human-dog interactions: Assessing motivation and mental state in a randomized, controlled trial - Fabio Carbone; Eve-Yaël Gerber; Camille Rérat; Jan Hattendorf; Karin Hediger (PLoS ONE, 2025)
Animal Assisted Interventions (AAIs) have been shown to have several effects in humans but the underlying cerebral mechanisms are still widely unknown. This research explored the neurological aspects of human–animal interactions. Specifically, we focused on frontal alpha asymmetry (FAA), a feature indicating differences in alpha power between the left and right frontal cortex, which is recognized as a correlate of approach motivation and positive affect. Twenty-nine healthy adults participated in this study, in which we used electroencephalography to measure their brain activity. The study comprised five phases: baseline measurements, interaction with a real dog, interaction with a replica dog, interaction with a plant, and a neutral phase. Participants had both physical and visual contact with the real dog, the replica and the plant, and the procedure was repeated three times for each participant. We also assessed participants’ subjective experiences of mental states and intrinsic motivation through the Multidimensional Well-Being and the Intrinsic Motivation Inventory questionnaires. The objective measurements of motivation and positive affect through FAA did not show a significant difference between interactions with a real dog and control conditions, but the subjective assessments differed. Participants reported significantly higher motivation and a more positive state of mind after interacting with a real dog compared to the control conditions. These results could be considered in therapeutic settings when determining whether to incorporate an animal into a treatment plan. In summary, this study highlights the complexity of human–animal interactions (HAI) and shows an intricate interplay between objective and subjective measurements. Our findings emphasize the importance of considering both neural markers and subjective experiences for understanding the nuanced mechanisms involved in the meaningful connections humans have with animals.